Impact of hydropower reservoirs on floods: evidence from large river basins in Austria. Issue 14 (26th October 2022) - Stecher, Gabriel; Herrnegger, Mathew
ABSTRACT: In this study the impact of hydropower reservoirs on floods is systematically assessed for eight heavily modified river basins in Austria. Since little discharge data from prior to the construction is available, unaffected annual peak discharges downstream of the reservoirs were estimated by transposing the peak runoff of an unaffected catchment, considering the spatial proximity, the catchment area and the temporarily corresponding precipitation conditions. Comparing the observed and estimated discharge, results show significant reductions not only at gauges directly affected by the reservoir but also farther downstream at receiving rivers. The propagation of the flood peak reduction downstream is also related to catchment area and reservoir characteristics. Extreme events with return periods greater than 30 years show a noteworthy flood peak reduction of over 33% on average. These findings show that reservoirs primarily constructed for hydropower generation also contribute significantly to flood control and flood mitigation.